Coenzyme Q10: an independent predictor of mortality in chronic heart failure. - Molyneux, S; Florkowski, C; George, P; Pilbrow, A; Frampton, C; Lever, M; Richards, A (2008)
OBJECTIVES: The aim of this study was to investigate the relationship between plasma coenzyme Q(10) (CoQ(10)) and survival in patients with chronic heart failure (CHF). BACKGROUND: Patients with CHF have low plasma concentrations of CoQ(10), an essential cofactor for mitochondrial electron transport and myocardial energy supply. Additionally, low plasma total cholesterol (TC) concentrations have been associated with higher mortality in heart failure. Plasma CoQ(10) is closely associated with low-density lipoprotein cholesterol (LDL-C), which might contribute to this association. Therefore we tested the hypothesis that plasma CoQ(10) is a predictor of total mortality in CHF and could explain this association. METHODS: Plasma samples from 236 patients admitted to the hospital with CHF, with a median (range) duration of follow-up of 2.69 (0.12 to 5.75) years, were assayed for LDL-C, TC, and total CoQ(10). RESULTS: Median age at admission was 77 years. Median (range) CoQ(10) concentration was 0.68 (0.18 to 1.75) micromol/l. The optimal CoQ(10) concentration for prediction of mortality (established with receiver-operator characteristic [ROC] curves) was 0.73 micromol/l. Multivariable analysis allowing for effects of standard predictors of survival--including age at admission, gender, previous myocardial infarction, N-terminal peptide of B-type natriuretic peptide, and estimated glomerular filtration rate (modification of diet in renal disease)--indicated CoQ(10) was an independent predictor of survival, whether dichotomized at the ROC curve cut-point (hazard ratio [HR]: 2.0; 95% confidence interval [CI]: 1.2 to 3.3) or the median (HR: 1.6; 95% CI: 1.0 to 2.6). CONCLUSIONS: Plasma CoQ(10) concentration was an independent predictor of mortality in this cohort. The CoQ(10) deficiency might be detrimental to the long-term prognosis of CHF, and there is a rationale for controlled intervention studies with CoQ(10).